Bawang Merah Goreng (Bareng Dio) Sebagai Bentuk Diversifikasi Inovasi Produk Umkm Budidaya Bawang Merah Puspita Makmur Nganjuk - Hendra Maulana; Siti Mi’Danur Rahmah; Afandy Yosediputra; Fatma Endah Cahyaningrum; Nina Zenitha Sekar Sari; Vivi Aprilliya Ningsih (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Shallots are a spice plant that is very easy to find in various regions, especially in Nganjuk Regency. Red onion is a commodity with a short shelf life. The tubers rot easily due to their high water content. During the main harvest, red onion production is abundant, the selling price drops, causing losses to farmers. To overcome this, it is necessary to manage red onions, including making fried shallots because fried shallots are often used by the community as a cooking spice or as a complement to the daily food menu. This phenomenon is utilized by Puspita Makmur managers to produce preparations from shallots. The KKN-T 67 Musir Kidul group helps Puspita Makmur MSMEs to attract public interest so that they can reach all groups by innovating product diversification. The product made is in the form of making Fried Shallot products.